Actuarial Aspects in Life Insurance - Muhammad Risalah; Nur Ahmadi Bi Rahmani (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The emergence of various syriah financial institutions (banks and non-banks) shows us that people are increasingly trusting in the sharia system. In connection with the number of financial institutions such as sharia insurance, both general and life insurance, it provides a lot of job opportunities. Therefore, it is necessary to have good quality human resources (HR). Human resources are an important element in a company, because this element is the part that drives the system in a company in order to achieve company goals. Insurance companies, both general and life itself, cannot be separated from the performance of actuaries. This type of research is descriptive with a qualitative approach. Data collection used by using interviews, study documentation and observation. The study in this research is to find out "Actuarial Aspects in Life Insurance". The results showed that actuaries of life insurance and pension plans have always had a special interest in the development and construction of mortality/death tables. Whole life insurance is insurance that provides protection for 99 years. 99 years is called a lifetime because in Indonesia the life expectancy of people is 65 years (men) and 70 years (women), so 99% of you will get coverage if you take this insurance.